Effect of Compressed Natural Gas Mixing on the Engine Performance and Emissions - M. M., Noor; Talal, Yusaf; Baker, P.; Hamawand, I. (Universiti Malaysia Pahang, 2013)
Cleaner air quality is becoming a global concern, thus to improve the fuel and combustion process is vital. In this paper, computational fluid dynamics (CFD) analysis software CFD-ACE is used to investigate the flow behavior of methane and air in a compressed natural gas (CNG)–air mixer to be implemented in a CNG–diesel dual-fuel stationary engine. The effect of the number of mixer holes on the mixture quality was evaluated. The results of the 3D CFD simulation showed that the 8-hole Venturi mixer gave superior performance compared to the 4-hole mixer. Further analysis was carried out on the 8-hole Venturi mixer to investigate the effect of engine speed on the mass flow rate of CNG and the equivalence air to fuel ratio (1/). The second half of the paper presents comparative performance results between a single cylinder research compression ignition (CI) engine fueled with a CNG–diesel system and a conventional CI engine fueled by conventional diesel. The engine was equipped with the simulated 8hole Venturi mixer. The result showed a significant reduction in exhaust gas emission components (NOx, CO and CO) from the CNG–diesel engine compared to the conventional diesel engine, i.e. the reduction rates were on average of 54%, 59% and 31% respectively. The average power output developed by the dual-fuel engine was 10% higher than the diesel over the power curve.